2016
DOI: 10.1007/5584_2016_52
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Autolysis During Flagella Insertion in Gram-Negative Bacteria

Abstract: The flagellum is an important macromolecular machine for many pathogenic bacteria. It is a hetero-oligomeric structure comprised of three major sub-structures: basal body, hook and thin helical filament. An important step during flagellum assembly is the localized and controlled degradation of the peptidoglycan sacculus to allow for the insertion of the rod as well as to facilitate anchoring for proper motor function. The peptidoglycan lysis events require specialized lytic enzymes, β-N-acetylglucosaminidases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 88 publications
0
44
0
Order By: Relevance
“…Six unique LT catalytic folds are known in Gram-negative bacteria, with each annotated as a conserved domain in the Pfam database (Figure 3). These six domains were organized previously into six distinct families (Herlihey & Clarke, 2016). LTs may be further organized by their substrate preference for either exolytic or endolytic strand cleavage.…”
Section: A Large Diverse Family Of Lts Has Evolvedmentioning
confidence: 99%
See 4 more Smart Citations
“…Six unique LT catalytic folds are known in Gram-negative bacteria, with each annotated as a conserved domain in the Pfam database (Figure 3). These six domains were organized previously into six distinct families (Herlihey & Clarke, 2016). LTs may be further organized by their substrate preference for either exolytic or endolytic strand cleavage.…”
Section: A Large Diverse Family Of Lts Has Evolvedmentioning
confidence: 99%
“…Further studies revealed that SltF interacts with FlgJ to excavate the cell wall for the insertion of the flagellum protein edifice through the sacculus (de la Mora et al , 2007). Herlihey and Clarke assigned SltF to the new subfamily 1F of Family 1 based on sequence analysis (Herlihey & Clarke, 2016). The Pfam database recognizes the catalytic domain of SltF as a Family 1 SLT domain (Pfam: PF01464).…”
Section: Gram-negative Family 1 Lytic Transglycosylasesmentioning
confidence: 99%
See 3 more Smart Citations